Ethnomathematics of Lahbako Dance Movement In The Perspective Of Mathematical Literacy Of Geometry Concept - Wardah, Nabilahdhia Rahayu Prima; Panglipur, Indah Rahayu; Putra, Eric Dwi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
Movement in a dance is a visual symbol full of meaning conveyed to be accepted by dance lovers from the whole dance performed. The selection of dance movements is related to the mathematical concept of illustrating its meaning (ethnomathematics). In addition, there is a mathematical literacy process of geometry concepts revealed in dance movements. This becomes a meaningful symbol that becomes a wealth of dance movements that are increasingly interesting to present. The purpose of this research is to identify the ethnomathematics of lahbako dance in the perspective of mathematical literacy of geometry concepts. qualitative research with a descriptive approach to explain the data and its discussion. Data collection methods of interviews, observation, and documentation with data validity test source triangulation. Subjects 2 people from Arutala dance studio and Hastarini. The results obtained are dance movements that come from different habits and interpretations of dancers but the actual meaning of the movements is the same. Ethnomathematics in lahbako dance successfully illustrates the meaning of the movements conveyed in lahbako dance through hand, finger, foot, and body movements that modify into lines, acute and obtuse angles, and triangular and rectangular fields. The mathematical literacy perspective of the geometric concepts of lines, angles, and fields is visualized conceptually, the application of real contexts of daily life, geometric thinking, and the delivery of mathematical language helps in illustrating the message conveyed in a lahbako dance, namely the activities of tobacco farmers. Further research recommendations for dance movements that jump or repeatedly back and forth and the count used by dancers in each movement.